Efeito da adição de elementos de liga nas propriedades mecânicas a quente de ferros fundidos cinzentos aplicados a discos de freio - Tuzzin, Matheus (My University, 2026)
The present work evaluated the impact of metallurgical modifications on a grey cast iron FC200 intended for brake disc applications through the controlled addition of alloying elements: chromium (0.15 wt. %), vanadium (0.10 wt. %), molybdenum (0.30 wt. %), copper (0.15 wt. %), and niobium (0.07 wt. %). Compared to the base alloy, the modified alloy exhibited superior mechanical properties, with a 70 % increase in tensile strength at room temperature and an average gain of 79 % under elevated temperatures over the entire temperature range evaluated. In addition, the modified alloy demonstrated enhanced high-temperature mechanical stability, with only a 1 % reduction in tensile strength up to 250 °C, compared to a 12 % loss observed in the base alloy. Brinell and Vickers hardness values increased by an average of 34 % and 46 %, respectively. Microstructural analysis revealed a 54.5 % reduction in the ferrite fraction (from 1.1 % to 0.5 %) and an increase in the pearlite volume fraction (from 86.6% to 89.3%), confirming the formation of a predominantly pearlitic matrix. This microstructural modification was accompanied by refinement effects, evidenced by a reduction in the graphite fraction from 12.4 % to 10.2 % and an increase in the number of fine graphite flakes. Regarding in-service performance, thermal fatigue resistance increased by 56 % at crack initiation and by 16 % at catastrophic failure. The results demonstrate that the proposed metallurgical modifications led to a material with superior mechanical performance, characterized by improved mechanical stability and enhanced thermal fatigue resistance for high-demand brake disc applications. [resumo fornecido pelo autor]
O presente trabalho avaliou o impacto de modificações metalúrgicas em um ferro fundido cinzento FC200 destinado à aplicação em discos de freio, por meio da adição controlada de elementos de liga: cromo (0,15 %), vanádio (0,1 %), molibdênio (0,3 %), cobre (0,15 %) e nióbio (0,07 %), todos em porcentagem em peso. Comparada à liga base, a liga modificada apresentou propriedades mecânicas superiores: a resistência à tração aumentou 70 % em temperatura ambiente, mantendo um ganho médio de 79 % a quente em toda faixa de temperatura, e demonstrou estabilidade nas propriedades mecânicas a quente, com apenas 1 % de perda de resistência até 250 °C (contra 12 % da liga base). As durezas Brinell e Vickers também cresceram, em média, 34 % e 46 %, respectivamente. A microestrutura da liga modificada revelou uma redução de 54,5 % na fração de ferrita (de 1,1 % para 0,5 %) e um aumento na fração volumétrica de perlita (de 86,6 % para 89,3 %), confirmando a formação de uma matriz predominantemente perlítica. Essa alteração foi acompanhada por um refinamento microestrutural, evidenciado pela redução do teor de grafita de 12,4 % para 10,2 % e pelo aumento no número de veios finos. No desempenho em serviço, a resistência à fadiga térmica aumentou 56 % na iniciação de trincas e 16 % na falha catastrófica. Conclui-se que as modificações metalúrgicas promoveram um material com desempenho mecânico superior, caracterizado por maior estabilidade mecânica e resistência à fadiga em aplicações de alta exigência. [resumo fornecido pelo autor]
Keywords: Ferro fundido; Microestrututra; Desgaste mecânico; Metais - Fadiga; Materiais; Cast-iron; Microstructure; Mechanical wear; Metals - Fatigue; Materials